Kant e o fundamento da moralidade: um estudo da dedução do imperativo categórico em GMS III - Ribeiro, Elton Cândido (2016)
This work aims to study the deduction of the categorical imperative in the third section of Kant’s Groundwork for the Metaphysics of Morals. Undoubtedly, this deduction is an important Kantian attempt to offer a foundation for his a priori ethics. More than two centuries later, there is no consensus among scholars and commentators regarding what is the structure of the argument, as well as its aim and its importance in the Kantian Critical Philosophy. This thesis is structured in three chapters. The first chapter studies the analysis of the concept of “good will” in the first section of Groundwork. The second chapter follow the analysis of the concept of “finite rational agent” in the second section. Lastly, the third chapter studies the deduction of the categorical imperative in the third section of Groundwork. The argument of the deduction is comprised in the following steps: the analytical relationship between liberty and morality; the presupposition of the effectiveness of the liberty of all rational being; the presupposition of the effectiveness of the liberty of the rational-sensitive being; the deduction of the categorical imperative